Families and family values in society and culture - Albert, Isabelle; Emirhafizovic, Mirza; Shpigelman, Carmit-Noa; Trummer, Ursula (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"This book which has been created in the framework of the EU-funded COST Action INTERFASOL brings together researchers from 22 INTERFASOL countries, who frame intergenerational family solidarity in the specific historical, cultural, social and economic context of their own country. Integrating different perspectives from social and political sciences, economics, communication, health and psychology, the book offers country-specific knowledge and new insights into family relations, family values and family policies across Europe"-- Provided by publisher.
Keywords: Families -- Europe.; Family policy -- Europe.; Social Science -- Sociology -- Marriage & Family.; Sociology: family and relationships.; Wedding, Marriage.; elektronické knihy; electronic books